2015
DOI: 10.9734/ijbcrr/2015/9806
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity of Ethanolic Leaf Extracts of Spilanthes uliginosa, Ocimum basilicum (Sweet Basil), Hyptis spicigera and Cymbopogon citratus on Mice Exposed to Plasmodium berghei Nk 65

Abstract: In Africa and elsewhere, medicinal plants including Spilanthes uliginosa, Ocimum basilicum, Hyptis spicigera and Cymbopogon citratus are still widely used in the treatment of malaria and other ailments. The aim of the present study was to investigate in vivo antiplasmodial effect of ethanolic leaf extract of these plants in mice. Oral acute toxicity of the extracts was evaluated in mice using modified Lorke's method and their in vivo anti-plasmodial effect against early infection, curative effect against estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…However, the definite mode of actions of the extract's oil has not been established but the mechanism suggested here in the study can not be discarded (Ogunwande et al, 2010, Victor andDavid, 2015). This observation is in line with the report of Uraku et al (2015a) and Balamurugan et al (2012). The active principle, area of peak concentration (%), Retention Time (RT) Molecular Weight (MW) and Molecular Formula (MF) in the methanol extract as identified through the NIST database are listed in Table 1.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, the definite mode of actions of the extract's oil has not been established but the mechanism suggested here in the study can not be discarded (Ogunwande et al, 2010, Victor andDavid, 2015). This observation is in line with the report of Uraku et al (2015a) and Balamurugan et al (2012). The active principle, area of peak concentration (%), Retention Time (RT) Molecular Weight (MW) and Molecular Formula (MF) in the methanol extract as identified through the NIST database are listed in Table 1.…”
Section: Resultssupporting
confidence: 83%
“…Plants are considered as one of the most valuable sources of food, medicine and drug for prevention of illness and maintenance of human health (WHO., 2003). In Nigeria, many indigenous plants are broadly consumed as food or home remedies especially for the treatment or management of common diseases and some of these ailments have no cure with the use of synthetic drugs (Uraku et al, 2015a). The importance of plants in medicine remains even of greater relevance with the current global shift to obtain drugs from plant sources, as a result of which attention has been given to the medicinal value of herbal remedies for safety, efficiency and economy (Uraku et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…This findings correlates with the report by Mbaka et al [21], which reported a significant (P < 0.05) weight gain in both treated and control groups in the animals treated with extract of Sphenocentrum jollyanum leaves. This result also agrees with that of Uraku et al [22] which reported general decrease in average body weight of the untreated mice on the 7th day relative to those treated with the leaf extracts of S. uliginosa, O. basilicum, H. spicigera and C. Citrates. By visual observation, the extract appeared to have stimulated the appetite of the mice thereby increasing the amount of food and water consumed and which might be responsible for increase in the body weight of the treated mice.…”
Section: Discussionsupporting
confidence: 93%
“…The family-wise analysis showed that the family Amaranthaceae held the dominant position by representing more number of species (13 species). Habit-wise analysis shows that maximum representatives to the plants are from herb (76) community, followed by trees (22), shrubs (17), climbers (6), parasitic shrub and parasitic twinner (1), and fern (1). The absence of epiphytes indicates the loss special habitats due to the degraded status of the hill.…”
Section: Resultsmentioning
confidence: 99%
“…The close association between the human and plants has evolved over generations of experience. This trend has been continued to the present time where people get much of their needs, particularly, the food and medicine from biological resources [1].…”
Section: Introductionmentioning
confidence: 99%